Physico-chemical and mineralogical characteristics of Rudua Soil Series - Khairuanuar, Norakmal (2015)
Sandy soils are known to have low soil fertility level and less suitable for agriculture purposes. However, in Malaysia, the distributions of sandy soils are huge especially at the coastal area of Peninsular Malaysia. The soils in this area are locally known as Beach Ridges Interspersed with Swales (BRIS) soils. The characteristics of these soils include low percentage of clay content, high porosity, high leaching, low water retention and lack of soil nutrients which makes it less favorable for crops to grow and survive. As it covered a large area of coastal area of Peninsular Malaysia, government has now encouraged farmers to develop these soils mainly for agriculture purposes. Hence, a study was conducted to determine the physico-chemical properties and mineralogy of these soils which is by taking different soil depth of Rudua Soil Series as treatments. The study area was located in the Kelantan-Terengganu Coastal Plains, Peninsular Malaysia which is started from Bachok, Kelantan (in the north) to Merang, Terengganu (in the south). The Rudua Soil Series was identified and soil samples from four different soil depths were dug and brought to laboratory for further analysis. The physical properties, chemical properties and mineralogy identification analysis were carried out. The presences of light and heavy minerals in the soil were also determined. The results obtained show least different on physical properties as the sand contents were high. Whereas for chemical properties, the soils show an improvement. These are mainly caused by the application of fertilizer and additional of organic matter into the soils. As for the mineralogy identification, the minerals that are found in these soils are quartz, lepidocrocite, hematite, kaolinite, muscovite, microline, and variscite.